Apparent foreign-body-like structure detected in the left atrium after catheter ablation for persistent atrial fibrillation - Skala, Tomas; Moravec, Ondrej; Hutyra, Martin; Tudos, Zbynek; Kocher, Martin; Taborsky, Milos (Biomedical papers, 2019)
Background: A foreign body left in left atrium after catheter ablation of atrial fibrillation is a very rare complication. Nevertheless, there are no reports so far about a large newly emerged structure only giving the impression of being a foreign body left in the heart after catheter ablation. Case report: This report presents a case of a patient after catheter ablation for persistent atrial fibrillation. Because of atrial tachycardia during follow-up, patient was indicated for reablation. Imaging methods including intracardiac echocardiography showed a straw-like foreign body with the character of a transseptal sheath in left atrium. A cardiac surgery was performed with extraction of the foreign body. We found a fibrous chord-like material in the left atrium, microscopy showed myocardial tissue with continuous transition to fibrinous elastic vessel. No signs of foreign material were found. Conclusion: We have found a newly emerged body giving the impression of being of foreign origin in left atrium after catheter ablation of atrial fibrillation. Microscopy of the extracted material showed myocardial tissue with continuous transition to fibrinous elastic vessel and a fibrinous tissue with focal dystrophic calcification. Its origin remains unknown.
Keywords: catheter ablation; atrial fibrillation; cardiac surgery; foreign material; fibrinous tissue